Philosophical-anthropological view on higher education teacher professionalism and creativity - S.A., Borlakova; Klushina E.A., Klushina N.P.; Kharchenko L.N., Kotov S.V., Petrova N.P., Pivnenko P.P. (Opción, 2019)
The article presents the results of philosophical and anthropological view research on the professionalism and the creativity of a teacher of higher education. Content analysis has been selected and substantiated as a research methodology. Based on the data of scientific literature theoretical analysis and the conducted experiments, the concepts about the state of the psychological parameters of a higher education teacher personality were obtained, which make the basis of creativity. As a conclusion, they revealed and justified the dialectical interrelation and interdependence of a teacher’s creativity with his professionalism, and the state was also determined.